BALANCING THE SODIUM IN CRANIAL DIABETES INSIPIDUS AND RENAL SALT WASTING - Mk, Borhan; Tan, Florence Hs (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Disorder of water and sodium homeostasis can occur with sellar and suprasellar lesion. Cranial diabetes insipidus (CDI) is a common complication, characterized by polyuria, dehydration and hypernatremia. The use of cisplatin for intracranial malignancy can cause renal tubular dysfunction resulting in renal salt wasting (RSW), presenting similarly as polyuria, hypovolaemia, but with hyponatremia instead. The diagnosis and management of co-existing CDI and RSW can be challenging. We report a case of pineal germinoma with CDI and concurrent cisplatin-induced RSW. RESULTS A 17-year-old male was admitted for recurrent seizure episodes and headache. His vital signs and electrolytes were normal. He has under-developed secondary sexual characteristics. Hormonal workup confirmed panhypopituitarism, and he received levothyroxine and hydrocortisone replacement. Pituitary MRI revealed pineal lesion with sellar and suprasellar extension. Endoscopic ventriculostomy and biopsy reported as germinoma. Postoperatively, he developed polyuria with hypernatremia of 167 mmol/L. A diagnosis of CDI was made and he responded well to desmopressin and required maintenance dose at 0.1 mg TDS. Subsequently, he received cisplatinbased chemotherapy. While on chemotherapy, despite usual replacement dose for desmopressin, levothyroxine and hydrocortisone, he developed polyuria (up to 5L/day), hypotension (BP 98/50 mmHg) and tachycardia (pulse 104 beats/minute). Laboratory results showed hyponatremia of 130 mmol/L, raised urine sodium (125 mmol/L) and urine osmolality (397 mOsmol/kg). Diagnosis of cisplatininduced RSW was made. His desmopressin dose was maintained but intravenous isotonic saline and regular oral nutritional supplements was initiated to replace sodium and fluid loss. Post-chemotherapy, his serum sodium normalised with resolved polyuria. CONCLUSION Misinterpretation of recurring polyuria or hyponatremia in patient with CDI as under or over replacement with desmopressin can cause morbidity as treatment for CDI and RSW differs. Adequate fluid and salt replacement is the main treatment in RSW. Hydration status, laboratory investigations, especially urine osmolality and urine sodium, and regular serum sodium monitoring, can guide in early diagnosis and proper therapy.